Factors and conditions of transformation of the world oil market - K. A. Turkeeva; A. Sh. Suleimenova (Экономика: стратегия и практика)
The article analyzes the global oil market, determines what factors and conditions affect its transformation. The situation in the oil market is developing in such a way that the price is the main indicator in the transformation of the world oil market. The article focuses on global oil production and global oil consumption, which are dependent on the price environment. That is, the conjectural factor that is most well-known in the development of the oil market and is associated with changes in world production (supply), consumption (demand), which dictates price offers. At the same time, there are significant price fluctuations and caused by other factors that affect the transformation of the world oil market, such as: economic factors, geopolitical factors, as well as technological factors.The purpose of the article is to determine the transformational factors of the world oil market in the conditions of shock conditions that occurred in the conditions of price “collapses” in the market, leading to sharp and significant changes in the entire world economic system.Methodological tools of scientific articles are based on an integrated approach of analysis of the world oil market based on scientific research methods, which include methods of system approach, comparative analysis, synthesis, empirical research - systematization, economic and statistical groups, as well as historical-logical method.